Development of the game-based pre-screening test for students with dyslexia - Athirah Syahida, Mohd Tarmezi; Siti Suhaila, Abdul Hamid; Nabilah Filzah, Mohd Radzuan; Zahian, Ismail; Adzhar, Kamaludin; Muhammad 'Arif, Mohamad; Murni, Mahmud (Science & Knowledge Research Society, 2023)
The conventional approach to screening dyslexia occurrence in Malaysia includes identifying issues by parents or teachers on their childrens performance in spelling, reading, writing, and mathematical understanding. One of the mediums is using the checklist instrument for dyslexia (ISD) developed by the Ministry of Education (MoE) Malaysia under the Special Education Department. It is the first step in identifying children who may have dyslexia. However, the screening needs to be conducted through a written test using paper and pencil. It requires the children to sit and answer the test in an exam setting. This makes the children feel stressed, being judged and monitored for the whole session. The operation of ISD also requires experienced teachers and it becomes difficult if he/she is a new teacher and has not been exposed to identifying dyslexia. Therefore, this project suggesting to overcome the problems through a “Game-Based Dyslexia Pre-Screening Test" which screened the children with or without dyslexia by answering a few questions derived from the ISD and Malay language textbooks standards 1 to 3 while the children played a game. This application allows children to play while going through the test with more fun and enjoyment, and increases their interest to play without knowing they are being assessed. In this project, interviews and surveys were conducted with teachers and parents at the beginning of the project. Design and development of the game include Unity, Visual Studio, and several other applications that were used to produce this project. Finally, evaluation using the Software Usability Scale (SUS) and observation of 30 students showed positive feedback. All of them liked playing the games, and they were engaged in playing the game which was assessed using times taken. This game can be a pre-screening approach to evaluate the students without making the students depressed or feeling different from their peers.